Synthesis, characterization, crystal structure, in silico and computational studies on a novel Schiff base derived from α-chlorocinnamaldehyde and 4-aminoantipyrine - Adimudo, Hillary Chijioke; Agu, Chidike Justus; Okenyeka, Obinna U.; Eddy, Nnabuk O.; Dim, Ebubechukwu Nnamdi; Dege, Necmi; Bonardd, Sebastian; Vanka, Kumar; Ibezim, Akachukwu; Idika, Digbo Iku; Diaz, David Diaz; Obasi, Nnamdi Lawrence (Journal of Molecular Structure, 2023)
Schiff base, 4-(((1E,2Z)-2-chloro-3-phenylallylidene)amino)-1,5-dimethyl-2-phenyl-1,2 -dihydro-3H-pyrazol-3-one (1) was synthesized by condensation reaction of 4-aminoantipyrine and & alpha;-chlorocinnamaldehyde. The compound was characterized using Fourier-transform infrared spectroscopy (FT-IR), ultraviolet (UV)-visible spectroscopy, proton and carbon nuclear magnetic resonance spectroscopy (1H/13C NMR) and single-crystal X-ray diffraction analysis (SC-XRD). Density functional theory (DFT) was used to compute molecular parameters and also compared them with experimental data. The X-ray diffraction data revealed that the compound crys-tallizes as a monoclinic crystal system with a space group of C2/c and Z = 8, and is stabilized by C12-H12MIDLINE HORIZONTAL ELLIPSISO1, and C8-H8AMIDLINE HORIZONTAL ELLIPSISO1 intramolecular hydrogen bonds. The presence of a distinctive azomethine C = N bond length N3-C12 of 1.283(3) & ANGS;, and 1640 cm-1 stretching vibration in the FT-IR spectrum are evidence of the formation of a Schiff base. The computational result indicates that the ionization energy (IE), and electron affinity (EA) values for the molecule are 4.025 and 2.110 eV, respectively. The positive value of EA suggests that the addition of an electron to the molecule would be an exothermic process. The evaluated energy is relatively low and is an expression of the ease of electron transfer from the highest occupied molecular orbital (HOMO) to the lowest unoccupied molecular orbital (LUMO). Hirsfeld surface map over dnorm and curvedness surface indicated the presence of 7C-7C stacking while the shape factor index suggests donor and acceptor intermolecular C-H-7C. Analysis of Hirsfeld surfaces concerning the fingerprint indicated a minimal contribution from the de -di pair and reveals H–H as a major contribution to the Hirsfeld surface. However, the molecular packing did not confirm H–H as a significant contributor the packing. Docking calculations on the compound showed average theoretical binding energies toward aromatase (-5.99 & PLUSMN; 0.34 kcal/mol) and fibroblast growth factor receptor (FGFR) (-17.57 & PLUSMN; 6.85 kcal/mol), indicating binding interactions with both protein targets.
Keywords: Computational studies; molecular modeling; Schiff base; X-ray crystallography